2019
DOI: 10.1111/ecc.13096
|View full text |Cite
|
Sign up to set email alerts
|

“An Ambition to Make People Feel at Home” or “The Emperor’s New Clothes”? Professional stakeholder views of wellness centres in cancer care

Abstract: Objective Wellness centres offer people affected by cancer to access to information and services in a supportive environment. This study aimed to understand stakeholder opinions and perspectives about the potential of wellness centres to contribute to cancer care. Methods This study adopted a qualitative approach with health professionals, leaders of key cancer organisations and cancer policy stakeholders interviewed. Results were analysed with thematic analysis. Results Twenty‐three stakeholders representing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A study that interviewed professional stakeholders’ views of wellness centers concluded that wellness models do not have to meet all users’ needs but be to be able to link the person to options that may already exist – either in the clinical, community, charity, or government sectors. [ 11 ] This view was supported by participants in the current study that agreed on the need to obtain reliable information about treatment and support options. The topic of financial challenges came up as a consistent theme with participants in maintaining wellness during cancer treatment.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…A study that interviewed professional stakeholders’ views of wellness centers concluded that wellness models do not have to meet all users’ needs but be to be able to link the person to options that may already exist – either in the clinical, community, charity, or government sectors. [ 11 ] This view was supported by participants in the current study that agreed on the need to obtain reliable information about treatment and support options. The topic of financial challenges came up as a consistent theme with participants in maintaining wellness during cancer treatment.…”
Section: Discussionmentioning
confidence: 62%
“…Participants and families/friends in this study described a high value of social support provided from both health professionals and the community of the hospital in sustaining wellness. An environment that is welcoming and friendly[ 11 24 ] has been identified by participants in this study and in a previous study of 188 patients and carers as being a place that can be relaxing, where you can sit and have tea/coffee, and chat to other people and health professionals as a means of obtaining support to enhance wellness. [ 10 ] Accessible information enables people to increase personal control and be more proactive with wellness than sometimes actual face-to-face services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data analysis and data collection were conducted concurrently, and recruitment was ceased once data saturation had been achieved. The expected sample size was also informed by our previous qualitative research including health professionals interviews [25][26][27] and recommendations from the literature [28]. Qualitative description was used to examine and interpret participant's understanding of dietary patterns and current dietetic practice.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Ugalde and colleagues () adopt a qualitative approach to explore the promise and ambition of cancer wellness centres as an opportunity for community‐clinical engagement. This is a highly salient topic given the spread of such centres in contemporary clinical settings.…”
mentioning
confidence: 99%